2015
DOI: 10.3399/bjgp15x684373
|View full text |Cite
|
Sign up to set email alerts
|

Translation of clinical prediction rules for febrile children to primary care practice: an observational cohort study

Abstract: Study setting and selection of patientsThe out-of-hours healthcare system in the Netherlands and data collection of this study have been published previously. 15 In summary, all contacts of children <16 years that had taken place at five GP cooperatives (GPCs) of the Rotterdam Rijnmond-district (collaboration of >250 GP-practices) between March 2008 and February 2009 were selected. Eligible contacts were those concerning children who had a face-to-face consultation with the GP and reported fever as the reason … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…However, the clinical model did not perform equally well when externally validated, yielding AUC of only 0.60 (0.49–0.70) in the validation cohort ( 52 ). An updated version including ill clinical appearance increased the AUC to 0.69 (0.63–0.75) in derivation population and to 0.65 (0.62–0.67) when validated in an external dataset, although in primary care ( 54 ). Similarly, another clinical score developed by Brent et al ( 13 ) based on eight clinical variables showing moderate ability to predict SBI [AUC, 0.77 (0.71–0.83)] did not perform equally well when validated in external datasets ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the clinical model did not perform equally well when externally validated, yielding AUC of only 0.60 (0.49–0.70) in the validation cohort ( 52 ). An updated version including ill clinical appearance increased the AUC to 0.69 (0.63–0.75) in derivation population and to 0.65 (0.62–0.67) when validated in an external dataset, although in primary care ( 54 ). Similarly, another clinical score developed by Brent et al ( 13 ) based on eight clinical variables showing moderate ability to predict SBI [AUC, 0.77 (0.71–0.83)] did not perform equally well when validated in external datasets ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical decision rules (CDRs) can help clinicians to assess the probability that a patient has a particular condition. 11 They are used widely in medicine to inform decisions about investigation and management. 12 , 13 Mant and colleagues developed a CDR for heart failure by undertaking a systematic review that identified 11 prospective studies set in primary care.…”
Section: Introductionmentioning
confidence: 99%
“…5 van Ierland and colleagues assessed the applicability and diagnostic value of published CPRs for identifying serious infections in febrile children in primary care by validating them in 9794 children presenting in Dutch out-of-hours care. 6 They found 794 (8.1%) of children were referred to the emergency department, a reasonable proxy outcome for serious illness in primary care. The CPRs tested performed moderately at best and disappointingly all CPRs had low sensitivity (that is, poor rule out value) although several had high specificity (that is, good rule in value).…”
Section: Identifying Serious Infections In Primary Carementioning
confidence: 99%